CORRELATES OF CHARISMATIC LEADER BEHAVIOR IN MILITARY UNITS: SUBORDINATES' ATTITUDES, UNIT CHARACTERISTICS, AND SUPERIORS' APPRAISALS OF LEADER PERFORMANCE. - Shamir, B.; Zakay, E.; Breinin, E.; Popper, M. (Academy of Management Journal, 1998)
We tested several hypotheses derived from an extended version of Shamir, House, and Arthur's (1993) theory of charismatic leadership. We used three different samples of subordinates to assess leade...